Group theory and quantum mechanics - Tinkham, Michael (Dover Books on Chemistry Ser., 2003)
This graduate-level text develops aspects of group theory most relevant to physics and chemistry and illustrates their applications to quantum mechanics: abstract group theory, theory of group representations, physical applications of group theory, full rotation group and angular momentum, quantum mechanics of atoms, molecular quantum mechanics, and solid-state theory.1964 edition.